2017
DOI: 10.1002/chem.201702814
|View full text |Cite
|
Sign up to set email alerts
|

Long Straczekite δ‐Ca0.24V2O5⋅H2O Nanorods and Derived β‐Ca0.24V2O5 Nanorods as Novel Host Materials for Lithium Storage with Excellent Cycling Stability

Abstract: Nanorods of δ-Ca V O ⋅H O, a straczekite group mineral with an open double-layered structure, have been successfully fabricated by a facile hydrothermal method and can be transformed into the tunnel β geometry (β-Ca V O ) through a vacuum annealing treatment. The generated β-Ca V O still preserves the nanorod construction of δ-Ca V O ⋅H O without substantial sintering and degradation of the nanostructure. As cathode materials, both calcium vanadium bronzes exhibit high reversible capacity, good rate capability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…[10c] The gradual capacity increase in the second stage may have relation to high electrode polarization and Li + diffusion paths become more flexible with increased cycling numbers. [27] Similar phenomena have also been found in other vanadium bronze such as K 0.25 V 2 O 5 , [28] Mg 0.25 V 2 O 5 • H 2 O, [10b] Ca 0.24 V 2 O 5 [29] and NH 4 V 4 O 10. [11] In the meantime, it is observed that the Coulombic efficiency gradually increases along with the increment of current rate.…”
Section: Resultssupporting
confidence: 74%
“…[10c] The gradual capacity increase in the second stage may have relation to high electrode polarization and Li + diffusion paths become more flexible with increased cycling numbers. [27] Similar phenomena have also been found in other vanadium bronze such as K 0.25 V 2 O 5 , [28] Mg 0.25 V 2 O 5 • H 2 O, [10b] Ca 0.24 V 2 O 5 [29] and NH 4 V 4 O 10. [11] In the meantime, it is observed that the Coulombic efficiency gradually increases along with the increment of current rate.…”
Section: Resultssupporting
confidence: 74%
“…Compared with monovalent intercalated species (e.g., Li + , Na + ), the divalent metal ions bonded with oxygen atoms lead to stronger ionic bonds, which effectively prevents structural collapse. The Zn 0.25 V 2 O 5 · n H 2 O cathode was developed by Nazar and her co‐workers .…”
Section: Recent Progresses In Flexible Zibsmentioning
confidence: 99%
“…[8] Unfortunately,these electrodes suffer from either limited capacity or very poor cycling stability.Very recently,layered and hydrated V 2 O 5 derivatives (e.g. In addition, compared with monovalent alkali metal cations (e.g.Li + , Na + ,K + ), the divalent metal ions bonded with oxygen atoms can bring about stronger ionic bonds, [9] better binding the layers together, which effectively prevents structural collapse; 2) Thet endency of vanadium to exist in multiple oxidation states,h ence making it high capacity in principle;3 )The charge shield effect of the crystal H 2 O, which could reduce the effective charges of intercalated Zn 2+ ions,and thus enhance the capacity and rate performance. In addition, compared with monovalent alkali metal cations (e.g.Li + , Na + ,K + ), the divalent metal ions bonded with oxygen atoms can bring about stronger ionic bonds, [9] better binding the layers together, which effectively prevents structural collapse; 2) Thet endency of vanadium to exist in multiple oxidation states,h ence making it high capacity in principle;3 )The charge shield effect of the crystal H 2 O, which could reduce the effective charges of intercalated Zn 2+ ions,and thus enhance the capacity and rate performance.…”
mentioning
confidence: 99%